Aortic stenosis: factors that interfere with the evaluation of severity by the Doppler echocardiographic method - review article (Research, Society and Development, 2025)
The importance of timely diagnosis and treatment of Aortic Stenosis (AS) is consensual in cardiology, seeking to prevent the high morbidity and mortality of this disease. Although diagnostic tests are widely available, several factors can interfere with the correct classification of the severity of the disease. Therefore, echocardiographic parameters are part of a critical step to ensure optimal results. Objective: To describe the main factors that interfere in the assessment of the severity of aortic stenosis by diagnostic methods, mainly echocardiography. Methodology: Data processing was performed by gathering the main journals related to the health area, with keywords related to the main theme (aortic stenosis) and subsequent selection of 80 articles for analysis and construction of this review article. Results: The review exposes the various limitations in the assessment of the severity of aortic stenosis, namely: factors related to anatomy, technical issues, hemodynamic variables and/or patient comorbidities.Conclusions: Knowledge of possible diagnostic limitations is essential for specialists in the field, thus allowing a more critical analysis of echocardiogram results, as well as providing the physician with the opportunity to extend the investigation in cases of complementary exams that disagree with the history and clinical examination.